The Impact of Smoking Cessation Training-Counseling Programs on Success of Quitting Smoking in Patients with Acute Coronary Syndrome - Zeinab Kazemzadeh; Zahra Sadat Manzari; Saeed Vaghee; Mahmood Ebrahimi; Sayed Reza Mazlom (Mashhad University of Medical Sciences, 2016)
Background: The smokers who use supportive programs have a greater chance to quit smoking. Smoking cessation recommendation is one of the most important prevention and treatment methods mentioned in care guidelines provided for patients with acute coronary syndrome. Aim: The main objective of this study is to determine the effects of training-counseling programs on smoking cessation in patients with acute coronary syndrome. Method: In this randomized controlled clinical trial, 51 patients with acute coronary syndrome in Ghaem and Imam Reza hospitals in Mashhad, 2015, after filling the Multinational Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA) questionnaire, were categorized into two groups. Intervention group received smoking cessation training-counseling program and control group received some advices/recommendations to quit smoking. After a three-month telephone follow-up, smoking cessation standard questionnaire was filled for all patients. The data were analyzed using SPSS v11.5 and Chi-square test. Results: The age of study participants was 52.6± 7.9 and 56.2±12.3 for intervention and control group, respectively. According to Chi-square test, a significant difference was observed between intervention and control groups in first through fifth stages after the intervention in terms of  succeed to quit smoking (p